Aerospace series. Nuts, anchor, self-locking, air resistant, sealing, floating, two lug, with counterbore, in corrosion resisting steel, passivated, MoS2 lubricated. Classification: 900 MPa (at ambient temperature) / 235 °C. (31st January 2017) - British Standards Institution,
No abstract available